1997
DOI: 10.1074/jbc.272.18.11718
|View full text |Cite
|
Sign up to set email alerts
|

The Propeptide Binding Site of the Bovine γ-Glutamyl Carboxylase

Abstract: ␥-Glutamyl carboxylase is an integral membrane protein required for the posttranslational modification of vitamin K-dependent proteins. The main recognition between the enzyme and its substrates is through an 18-amino acid propeptide. It has been reported that this binding site resides in the amino-terminal third of the ␥-glutamyl carboxylase molecule (Yamada, M., Kuliopulos, A., Nelson, N. P., Roth, D. A., Furie, B., Furie, B. C., and Walsh, C. T. (1995) Biochemistry 34, 481-489). In contrast, we found the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
(18 reference statements)
4
30
0
Order By: Relevance
“…Previous work from our laboratory showed that limited trypsin digestion of GGCX results in a disulfide-linked 30 kDa amino-terminal and 60 kDa carboxyl-terminal fragments (16) (Figure 1, lane 3). Figure 1 (lane 4) shows that only the 60 kDa carboxyl-terminal tryptic fragment is sensitive to PNGase F digestion indicating, in agreement with our previous report (16), that N-linked glycosylation occurs only on the 60 kDa carboxyl-terminal tryptic fragment of GGCX. Asparagine 159 is the only potential glycosylation site in the 30 kDa amino-terminal tryptic fragment and these results indicate that it is not glycosylated in vivo.…”
Section: N-glycosylation Sites Of Ggcx Are Located On the Carboxyl-tesupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work from our laboratory showed that limited trypsin digestion of GGCX results in a disulfide-linked 30 kDa amino-terminal and 60 kDa carboxyl-terminal fragments (16) (Figure 1, lane 3). Figure 1 (lane 4) shows that only the 60 kDa carboxyl-terminal tryptic fragment is sensitive to PNGase F digestion indicating, in agreement with our previous report (16), that N-linked glycosylation occurs only on the 60 kDa carboxyl-terminal tryptic fragment of GGCX. Asparagine 159 is the only potential glycosylation site in the 30 kDa amino-terminal tryptic fragment and these results indicate that it is not glycosylated in vivo.…”
Section: N-glycosylation Sites Of Ggcx Are Located On the Carboxyl-tesupporting
confidence: 90%
“…Figure 1 demonstrates that PNGase F treated GGCX (lane 2) migrates faster than the untreated sample (lane 1) in SDS-PAGE analysis indicating that GGCX is an N-linked glycoprotein. Previous work from our laboratory showed that limited trypsin digestion of GGCX results in a disulfide-linked 30 kDa amino-terminal and 60 kDa carboxyl-terminal fragments (16) (Figure 1, lane 3). Figure 1 (lane 4) shows that only the 60 kDa carboxyl-terminal tryptic fragment is sensitive to PNGase F digestion indicating, in agreement with our previous report (16), that N-linked glycosylation occurs only on the 60 kDa carboxyl-terminal tryptic fragment of GGCX.…”
Section: N-glycosylation Sites Of Ggcx Are Located On the Carboxyl-tementioning
confidence: 83%
“…Nevertheless, a hydrophobic propeptide different from the commonly known mammalian propeptides appears to be present in the substrate of the Conus carboxylase (1, 10). Therefore, one might expect to find a propeptide-binding site on the dGC that is not homologous to the hGC-binding site but that is located in the same region we previously determined to be the location of the mammalian site (11). One major difference between the Drosophila and mammalian ␥-glutamyl carboxylases is that the dGC is 86 amino acids shorter than the human enzyme from the carboxyl terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we presented evidence that there is a disulfide bond in carboxylase between cysteine residues 99 and 450 (7,13). However, there is some disagreement about whether the disulfide exists (34).…”
Section: The Two-chain Carboxylase Is Joined By a Disulfide Bondmentioning
confidence: 99%
“…On the basis of affinity peptidesubstrate labeling, Yamada et al reported that the propeptide binds to the carboxylase between residues 50 and 225 (6). Propeptide cross-linking experiments from our laboratory suggested that the propeptide binding region of carboxylase is between residues 438 and 507 (7). Further studies employing site-directed mutagenesis showed that at least part of the propeptide binding region includes residues between 495 and 513 of the carboxylase (8).…”
mentioning
confidence: 99%